2023
DOI: 10.1002/eap.2813
|View full text |Cite
|
Sign up to set email alerts
|

Tidal channel meanders serve as stepping‐stones to facilitate cordgrass landward spread by creating invasion windows

Abstract: Understanding the mechanisms by which the geomorphic structures affect habitat invasibility by mediating various abiotic and biotic factors is essential for predicting whether these geomorphic structures may provide spatial windows of opportunity to facilitate range‐expansion of invasive species in salt marshes. Many studies have linked geomorphic landscape features such as tidal channels to invasion by exotic plants, but the role of tidal channel meanders (i.e., convex and concave sides) in regulating the Spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 65 publications
0
1
0
Order By: Relevance
“…However, the role of tidal channel meanders, specifically the convex and concave sides, in regulating the invasion of Spartina alterniflora , remains unclear. Ning et al (2023) found that lower hydrodynamic disturbance and bed shear stress, coupled with higher propagule pressure triggered by eddies due to the convex structure of channel meanders, facilitated Spartina seedling establishment and growth. These findings demonstrate that the meandering geomorphic structures of tidal channels could act as stepping stones to significantly facilitate the landward invasions of Spartina along tidal channels.…”
Section: Mechanisms Of Invasion Successmentioning
confidence: 99%
“…However, the role of tidal channel meanders, specifically the convex and concave sides, in regulating the invasion of Spartina alterniflora , remains unclear. Ning et al (2023) found that lower hydrodynamic disturbance and bed shear stress, coupled with higher propagule pressure triggered by eddies due to the convex structure of channel meanders, facilitated Spartina seedling establishment and growth. These findings demonstrate that the meandering geomorphic structures of tidal channels could act as stepping stones to significantly facilitate the landward invasions of Spartina along tidal channels.…”
Section: Mechanisms Of Invasion Successmentioning
confidence: 99%